Trend Of Water Quality Status In Kelantan River Downstream, Peninsular Malaysia - Arniza Fitri; Khairul Nizam Abdul Maulud; Dian Pratiwi; Arlina Phelia; Farli Rossi; Nur Zukrina Zuhairi (Civil Engineering Departement, Andalas University, 2020)
The issues of freshwater pollutions and the high demand of clean freshwater for daily human activities have forced developing countries such as Malaysia to continuously monitor the quality of the freshwater. The present study objective is to present the trend of water quality status in the Kelantan River downstream, Peninsular Malaysia from 2005 to 2018. Water samples were collected during dry and monsoon seasons from a sampling station located at downstream of the Kelantan River. Water quality parameters such as temperature, pH and dissolved oxygen (DO) were measured in situ while other parameters were analysed in the laboratory based on retrieved water samples. Water quality status was determined based on National Water Quality Standard (NWQS) for River in Malaysia by calculating the water quality index (WQI) according to the concentration of six water quality parameters involving pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), suspended solids (TSS) and Ammonia Nitrogen (AN). The results showed that Kelantan River had good water quality during the dry season classified in Class II at 2005. The water quality was found to be slightly lower during the monsoon season in year 2006. In addition, increasing the number of construction, human activities in the land use areas, land use changes and the sewage water from domestic, industrial, wet market and food outlets in the Kelantan State have declined the water quality in Kelantan River from Class II (in 2005) to Class III (in 2010 and 2011) and to become Class IV in 2017 to 2018. The results of the present study are expected to give valuable information for the water managers in order to deal with better strategies in controlling the quality of freshwater at the Kelantan River and minimize the incidence of pollution-oriented problems, thus the water can be utilized for various water uses with appropriate quality.